Investigation of Hematological and Biochemical Profiles of Tannery Workers Exposed to Chromium in Hazaribagh, Bangladesh - Rahman, Adua; Rahman, Md. Fahimur; Akther, Jobaida; Nurun Nabi, A. H. M.; N. Islam, Laila (International Journal of Environment, 2019)
Occupational exposure to chromium used in mineral tanning processes cause adverse health effects on workers of leather tanning industries. This study aimed to evaluate the hematological and biochemical profiles in tannery workers of Hazaribagh, Bangladesh compared with a control group. A total of 225 participants, 121 tannery workers and 104 controls, were enrolled. All subjects completed interviewer-administered questionnaires; their physical health was examined, blood samples were collected and the hematological and biochemical parameters were analyzed. The tannery workers had mean duration of work exposure at tanneries for 13.1±9.7 years, and working hours per day of 10.7±2.3 which were significantly higher than 7.6±2.2 of the controls. Previous results showed long-term exposed tannery workers had significantly higher serum chromium concentrations than controls. The tanners had dermatological problems, infections on body surfaces, and respiratory ailments, among other complaints. The red blood cell count, hematocrit (48.91 %) and mean corpuscular hemoglobin concentration (29.39 g/dL) were lower in tannery workers but hemoglobin (14.58±1.30 g/dL) was significantly lower than in the controls (15.96±0.88 g/dL). The tanners had significantly lower neutrophil (51.31 %), higher lymphocyte (41.82 %), monocyte (2.44 %) and eosinophil (4.17 %) counts. Their mean creatinine and alkaline phosphatase values were normal but markers of liver damage, alanine transaminase (42.7±39.3 U/L) and aspartate transaminase (44.3±20.5 U/L), and liver dysfunction marker - bilirubin (1.04±0.85 mg/dL) levels were significantly higher. These findings suggest that exposure to chromium poses serious threats to the health of tannery workers who are at risk of toxicity related liver damage and hematological disorders.